Palaeoenvironmental characterization of a crocodilian nesting site from the Late Cretaceous of Brazil and the evolution of crocodyliform nesting strategies - Marsola, Jï¿½lio C. de A.; Batezelli, Alessandro; Montefeltro, Felipe C. [UNESP]; Grellet-Tinner, Gerald; Langer, Max C. (Elsevier, 2016)
Despite the vast crocodyliform fossil record, little is known about the reproductive biology and nesting strategies of the extinct members of the group. Here we report a large accumulation of crocodilian fossil eggs from the type-locality of the baurusuchid Pissarrachampsa sera. Sedimentary facies and architectural elements of the site support a palaeoenvironmental model with a shallow lacustrine, playa-lake system interacting to ephemeral braided fluvial channels, with aeolian influence and development of sandy soils. The presence of pedogenic calcretes in the palaeosols indicates arid to semi-arid conditions. The crocodilian affinity of the eggs is supported by the thin eggshell which bears wedge-shaped shell units with tabular microstructures. Furthermore, taphonomic data support an autochthonous assemblage of eggs and skeletal remains, hinting at a monotypical stratigraphic horizon and suggesting P. sera as the egg-laying taxon. The repeated pattern of four (eventually five) eggs per clutch at the site demonstrates that P. sera laid fewer eggs compared to modern crocodilians, indicating that k-selected reproductive strategy pattern is pervasive in the fossil record of Notosuchia. In the crocodyliform phylogenetic framework, the k-strategy and the “egg clutch sizes” optimization of Notosuchia is opposite to the strategy with larger clutches consistently occurring in modern Crocodylia and Neosuchia, the sister clade to Notosuchia. Yet, the lack of data on more early-branching taxa renders unclear which pattern is plesiomorphic for Crocodyliformes as a whole.
Keywords: Adamantina Formation; Bauru Basin; Crocodilian fossil eggs; Late Cretaceous; Palaeoenvironment; Pissarrachampsa sera